Food services and customer loyalty in the hospitality industry - Vitor Roslindo Kuhn; Antônio Carlos Benetti; Sara Joana Gadotti dos Anjos (Tourism & Management Studies)
Understanding the needs and expectations of customers is a major competitive tool. Their perception of food service quality has been increasingly studied. An understanding of this topic can help managers to develop strategies to improve customer satisfaction and increase loyalty. The objective of the research is to verify the predictive power of food service quality elements on customer loyalty intentions. This research is exploratory with quantitative approach applied to a hotel in Balneário Camboriú. We used multiple regression analysis to achieve results. The constructs analysed were: Service Brigade; Management; Menu; Ancillary Services; and Physical Features, which did not prove to be significant to Loyalty. The most significant construct was Service Brigade, a finding consistent with studies that show that employee training is key to increase the level of satisfaction and loyalty.